ANALISIS KINERJA PELAKSANAAN PENYELIDIKAN EPIDEMIOLOGI KASUS DEMAM BERDARAH DENGUE DI PUSKESMAS ROWOSARI KOTA SEMARANG TAHUN 2017 - Ade Yuny Afriyanty; Septo Pawelas Arso; Putri Asmita Wigati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Puskesmas Rowosari ranks first highest case of DHF in Semarang City 2015 and 2016. One of prevention of dengue fever through Epidemiology Investigation (EI), EI DHF aims to track the patient and larva examination. This study aims to analyze the performance of EI implementation seen from several variables, knowledge, skills and abilities, resources, rewards and punishment, leadership, organizational structure, punishment, and motivation and officer behavior. This research is a qualitative with in-depth interview method to EI Officer at Puskesmas Rowosari and Puskesmas Bulusan, Head of Puskesmas, and officer of P2P VTZ DKK Semarang. The results performance is not optimal yet, not all cases in EI (> 24 hours), late delivering EI report (> 1x24 hours after EI), there are cases with buildings examined <20 buildings. This problem is influenced by officers who can not use HEWS, there is incomplete address so difficult to implement EI, support of head of health center is not given to all officers, no direct appreciation for officers from Puskesmas and DKK Semarang, the number of tasks assigned by Puskesmas EI officers so that EI is done outside of working hours of Puskesmas, staff motivation is still lacking, officer behavior is still lack in discipline and time management. Suggestions for the problem are DKK Semarang and Head of Puskesmas can give appreciation to encourage officer motivation, Head of Puskesmas can give support to the officers and officers can to set priorities on each task and be able to manage time. Implementation of EI can work with Gasurkes. Provision of additional duties on officers are expected to be adjusted to the task and task assignments that have been given.